Phylogenomic analysis of Calyptratae: resolving the phylogenetic relationships within a major radiation of Diptera. (22nd February 2019) - Narayanan Kutty, Sujatha; Meusemann, Karen; Bayless, Keith M.; Marinho, Marco A. T.; Pont, Adrian C.; Zhou, Xin; Misof, Bernhard; Wiegmann, Brian M.; Yeates, David; Cerretti, Pierfilippo; Meier, Rudolf; Pape, Thomas
Abstract: The Calyptratae, one of the most species‐rich fly clades, only originated and diversified after the Cretaceous–Palaeogene extinction event and yet exhibit high species diversity and a diverse array of life history strategies including predation, phytophagy, saprophagy, haematophagy and parasitism. We present the first phylogenomic analysis of calyptrate relationships. The analysis is based on 40 species representing all calyptrate families and on nucleotide and amino acid data for 1456 single‐copy protein‐coding genes obtained from shotgun sequencing of transcriptomes. Topologies are overall well resolved, robust and largely congruent across trees obtained with different approaches (maximum parsimony, maximum likelihood, coalescent‐based species tree, four‐cluster likelihood mapping). Many nodes have 100% bootstrap and jackknife support, but the true support varies by more than one order of magnitude [Bremer support from 3 to 3427; random addition concatenation analysis (RADICAL) gene concatenation size from 10 to 1456]. Analyses of a Dayhoff‐6 recoded amino acid dataset also support the robustness of many clades. The backbone topology Hippoboscoidea+(Fanniidae+(Muscidae+((Anthomyiidae–Scathophagidae)+Oestroidea))) is strongly supported and most families are monophyletic (exceptions: Anthomyiidae and Calliphoridae). The monotypic Ulurumyiidae is either alone or together with Mesembrinellidae as the sister group to the rest of Oestroidea. The Sarcophagidae are sister to Mystacinobiidae+Oestridae. Polleniinae emerge as sister group to Tachinidae and the monophyly of the clade Calliphorinae+Luciliinae is well supported, but the phylogenomic data cannot confidently place the remaining blowfly subfamilies (Helicoboscinae, Ameniinae, Chrysomyinae). Compared to hypotheses from the Sanger sequencing era, many clades within the muscoid grade are congruent but now have much higher support. Within much of Oestroidea, Sanger era and phylogenomic data struggle equally with regard to finding well‐supported hypotheses.